Bonjour,
méthode : AX = B
⇔ A⁻¹ x AX = A⁻¹ x B
⇔ X = A⁻¹ x B
A⁻¹ =
A⁻¹ x B₁ = 3 2 0 (en colonne)
A⁻¹ x B₂ = 1 1 1
A⁻¹ x B₃ = 2 1 -1
Copyright © 2025 ELIBRARY.TIPS - All rights reserved.
Lista de comentários
Verified answer
Bonjour,
méthode : AX = B
⇔ A⁻¹ x AX = A⁻¹ x B
⇔ X = A⁻¹ x B
A⁻¹ =![\left[\begin{array}{ccc}1&1&-1\\2&1&-3\\-1&-1&2\end{array}\right] \left[\begin{array}{ccc}1&1&-1\\2&1&-3\\-1&-1&2\end{array}\right]](https://tex.z-dn.net/?f=%5Cleft%5B%5Cbegin%7Barray%7D%7Bccc%7D1%261%26-1%5C%5C2%261%26-3%5C%5C-1%26-1%262%5Cend%7Barray%7D%5Cright%5D)
A⁻¹ x B₁ = 3 2 0 (en colonne)
A⁻¹ x B₂ = 1 1 1
A⁻¹ x B₃ = 2 1 -1